S3.3d Influenza versus COVID-19-associated pulmonary aspergillosis: Profiling lower respiratory tract epithelial and myeloid innate immunity in patient samples. (20th September 2022) - Feys, Simon; Gonçalves, Samuel M.; Khan, Mona; Choi, Sumin; Boeckx, Bram; Chatelain, Denis; Cunha, Cristina; Debaveye, Yves; Hermans, Greet; Hertoghs, Marjan; Humblet-Baron, Stephanie; Jacobs, Cato; et al.
Abstract: S3.3 Innate immune responses to pathogenic fungi, September 21, 2022, 4:45 PM - 6:15 PM: Objectives: Up to 20% and 15% of critically ill influenza and coronavirus disease 2019 (COVID-19) patients are affected by influenza- and COVID-19-associated pulmonary aspergillosis (IAPA and CAPA) respectively. These viral-fungal coinfections are difficult to diagnose and are associated with increased mortality. Mechanistic insights into the development of IAPA and CAPA are a prerequisite for the development of new biomarkers and novel immunomodulatory therapeutic targets. However, data on the pathophysiology are scarce. With this study, we aimed at expanding our knowledge of IAPA and CAPA pathophysiology in an explorative way, resorting to lower respiratory tract samples and focusing on the epithelial and myeloid innate immunity components of the antifungal host response. Methods: We performed nCounter gene expression analyses of 755 genes linked to innate immunity, and determined protein levels of 47 cytokines, chemokines, growth factors, and other inflammatory mediators on bronchoalveolar lavage (BAL) fluid samples from 166 ICU-admitted influenza and COVID-19-patients with or without aspergillosis. Additionally, we performed spatial transcriptomics and RNAscope on in vivo tracheobronchial biopsies from four IAPA and CAPA patients. Results: Several genes encoding proteins with important effector functions in antifungal immunity are downregulated in BAL fluid of IAPA and CAPA patients compared with influenza-only or COVID-19-only patients. Cellular deconvolution of the gene expression data reveals a significantly lower BAL neutrophil fraction in CAPA patients compared to COVID-19-only patients. IAPA and CAPA patients have high BAL fluid levels of pro-inflammatory cytokines, but these are not significantly different from the levels seen in influenza-only and COVID-19-only patients. By integrating the BAL fluid cytokine levels with their respective transcriptional responses, we show that IAPA patients, and to a lesser extent CAPA patients, have an aberrant transcriptional response to pro-inflammatory cytokines as well as type I and type II interferons, which may result in poor cellular effector functions (Fig. 1a). Interferon-gamma signaling is abrogated in both IAPA and CAPA patients when compared with influenza-only and COVID-19-only patients. We observe significantly higher levels of growth factors associated with lung fibrosis in both IAPA and CAPA BAL fluid, which may contribute to the higher mortality seen in these coinfections (Fig. 1b). Using spatial transcriptomics, we show that different epithelial defense mechanisms are at play in IAPA and CAPA (Fig. 2a). Finally, using RNAscope ultrasensitive single-molecule RNA in situ hybridization, we visualize fungal and viral co-localization in CAPA tracheobronchial tissue, proving that virus-induced epithelial barrier disruption paves the way for tissue-invasive aspergillosis (Fig. 2b). Conclusion: Using state-of-the-art techniques in lower respiratory tract samples obtained from a large representative patient cohort, we provide arguments for a three-level breach in antifungal immunity in IAPA and CAPA. A hampered ability to phagocytize and kill fungal spores enables Aspergillus germination and growth, leading to hyphae that are not contained because of restrained extracellular defense mechanisms. These hyphae may easily become tissue-invasive through an epithelium that is weakened by the viral infection, causing detrimental damage to the respiratory system. Functional studies will be necessary to further unravel the pathophysiology of IAPA and CAPA.